2022
DOI: 10.3389/fimmu.2022.1027472
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as immune regulators and biomarkers in tuberculosis

Abstract: Tuberculosis (TB), which is caused by Mycobacterium tuberculosis (Mtb), is one of the most lethal infectious disease worldwide, and it greatly affects human health. Some diagnostic and therapeutic methods are available to effectively prevent and treat TB; however, only a few systematic studies have described the roles of microRNAs (miRNAs) in TB. Combining multiple clinical datasets and previous studies on Mtb and miRNAs, we state that pathogens can exploit interactions between miRNAs and other biomolecules to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 249 publications
0
9
0
Order By: Relevance
“…Additionally, miRNAs can be delivered into or out of cells by vesicles, which could be detected in body fluids ( 44 ). In addition, miRNA profiles can be related to disease development or division among diseases with identical symptoms ( 45 , 46 ), demonstrating their clinical significance.…”
Section: The Functions Of Exosomal Ncrnasmentioning
confidence: 99%
“…Additionally, miRNAs can be delivered into or out of cells by vesicles, which could be detected in body fluids ( 44 ). In addition, miRNA profiles can be related to disease development or division among diseases with identical symptoms ( 45 , 46 ), demonstrating their clinical significance.…”
Section: The Functions Of Exosomal Ncrnasmentioning
confidence: 99%
“…In the realm of molecular biology, gene regulation plays a crucial role in maintaining cellular function and has been implicated in the pathogenesis of complex diseases like PTB 12 . Noncoding RNAs (ncRNAs), particularly long noncoding RNAs (lncRNAs) and microRNAs (miRNAs), have emerged as significant players in the immune response to PTB 13 . LncRNAs, for instance, are key regulators in the inflammatory response to infection, particularly influencing T cell responses 14 , while miRNAs have been increasingly recognized for modulating host-TB bacilli interactions through immune pathways 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The increased expression of circAGFG1 in alveolar lavage fluid of ATB patients can inhibit the apoptosis of M. tb-infected macrophages and promote autophagy through the circAGFG1/miR-1257/Notch2 axis ( Shi et al, 2020 ). NcRNAs also have the potential to serve as diagnostic markers, therapeutic targets or therapeutic evaluation indicators for TB ( Davuluri and Chauhan, 2022 ; Hemati et al, 2022 ; Liang et al, 2022 ; Wang L. et al, 2022 ; Wang Q. et al, 2022 ; Zhang et al, 2022 ). Studies found that the upregulated hsa_circ_0001953, hsa_circ_0009024, hsa_circ_051239, hsa_circ_029965 and hsa_circ_404022 and the downregulated hsa_circ_0001380 and hsa_circRNA_103571 in the serum and the downregulated NONHSAT101518.2, NONHSAT067134.2, NONHSAT148822.1, and NONHSAT078957.2 in serum exosomes could be used as potential biomarkers for patients with ATB disease ( Huang et al, 2018 ; Yi et al, 2018 ; Luo et al, 2020 ; Fang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%